2016
DOI: 10.1016/j.jcot.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic-based morphometric study of thoracic spine and its relevance to anaesthetic and spinal surgical procedures

Abstract: A thorough knowledge of anatomical and radiological characteristics of the spine and their variations is essential for the clinicians. Data collected in the present study provides baseline normative values in Indian population and will help in guiding safe and effective completion of both surgical and anaesthetic procedures in the thoracic spine. Computer software aided morphometric data can help in selecting appropriate size and optimal placement of the implant with minimal procedural difficulties and complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
7
12
1
Order By: Relevance
“…In the present study, transverse pedicle angles from T1 to T10 vertebrae were found to be more compared to studies performed on Caucasians. Our findings of the pedicles being angulated medially, postero-anteriorly, decreasing in the cephalo-caudad direction from T1 to T4, increasing slightly at T5, and then decreasing trend from T5 to T12, are similar to other studies from India [10,16,17]. The Caucasian studies show a gradually decreasing trend from T1 to T12 [19].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the present study, transverse pedicle angles from T1 to T10 vertebrae were found to be more compared to studies performed on Caucasians. Our findings of the pedicles being angulated medially, postero-anteriorly, decreasing in the cephalo-caudad direction from T1 to T4, increasing slightly at T5, and then decreasing trend from T5 to T12, are similar to other studies from India [10,16,17]. The Caucasian studies show a gradually decreasing trend from T1 to T12 [19].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in concurrence with other authors in that the risk of a cortical breach during pedicle screw insertion is highest from T3 to T8 levels using conventional techniques [17,[21][22][23]. Various modifications like the 'in-out-in' technique, medial margin targeting method, pedicle or transverse process hooks, extra-pedicular screw, cannulated screw, laminar screw, and the cortical bone trajectory method have been studied as safe alternatives for thoracic spine fixation [20,[24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This proposed method for investigating spinal instrumentation can be performed at any spinal level for experimenting on combinations of screw size, angulation, entry point validation, and so on. This can provide a useful means of teaching instrumentation techniques and considerations that cannot be demonstrated using two‐dimensional material alone (Kaur, Singh, Prasath, Magu, & Tanwar, ). Another advantage is the compatibility of necessary software tools with normal operating hardware.…”
Section: Discussionmentioning
confidence: 99%